Recommendations On The Fight Against Nosocomial Infections Compliance In Health Facilities Of Yaounde (Cameroon) - Ekanga, Georgette Ndongo; Gonsu Kamga, Hortense; Same Ekobo, Albert; Baiye , William; Ntsomboh-Ntsefong, Godswill; Essomba , Arthur; Nukenine, Elias (International Journal of Scientific Research and Management (IJSRM), 2019)
Background: Nosocomial infection’s (NIs) data are scarce in developing countries. In some of these countries, national guidelines for its prevention by health facilities have introduced surveillance recommendations including Infection Control Assessment Tool (ICAT). The aim of our study was to evaluate the compliance levels of NIs recommendations.Methodology: We conducted a cross-sectional study from September to December 2018 in 10 health facilities in Yaounde. A checklist with two modules from the ICAT (Health Facility information and Infection Control Program) was used to determine the degree of compliance towards the recommendations by performing interviews, observations and consultation of documents.Results: Sixty (60) % of health facilities are aware of the national guidelines and regulation on the fight against NIs but only 30% have adopted them.  Accreditation standards applicable to health facilities are not known by any of the health facilities. The recommendations concerning demographic characteristics, water supply and the general characteristics on rooms were generally respected (more than 50%) in 90% of the health facilities. 100% of health facilities had less than fifty (50)% compliance level for the fight against NIs recommendations with compliance levels below 15% for 50% of them. This worst compliance (less than 15%) was especially observed with recommended practices concerning responsibilities and authorities (40% of health facilities), functionality of infection and control committees (50% of health facilities), key personnel responsible for fight against NIs (30% of health facilities) and study of outbreaks and surveillance of NIs (100% of health facilities). Training programs on fight against NIs had better scores (30% of health facilities with more than 50% of compliance levels). The Fischer test shows that there is a significant relationship between the compliance with all these recommended practices and the health facility capacity (P= 0, 0476) .Conclusion: NIs control programs in Yaounde health facilities are insufficient. Awareness, training, promotion and follow-up actions are necessary for the understanding and adoption of recommendations on the monitoring of NIs.